ALAT BANTU MATRAS UNTUK PEMBELAJARAN SENAM GULING DEPAN DAN BELAKANG BAGI SISWA KELAS ATAS SEKOLAH DASAR - SYAM, ASRY; YASIN , ISMET; SYAHRUDDIN, SYAHRUDDIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
Floor exercise lessons, especially front and back tumbling, are not easy for elementary school students. Changing from stability to imbalance by rolling over is not a familiar activity. The aim of this research is to develop tools to make it easier for students to learn front and back rolls. The research method uses the ADDIE development model. The initial product test on a small scale was 16 class V students at SDN 89 Sipatana, Gorontalo City and on a large scale it was 20 class V students at SDN 96 Kota Utara. Data collection through expert validation and student questionnaires as an evaluation of product feasibility, research results of tilting mattress product tests in the